ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, DAN BIAYA OPERASIONAL BANK TERHADAP PROFITABILITAS BANK GO PUBLIC DI INDONESIA PERIODE 2000-2007 - Ervani, Eva (Universitas Negeri Semarang, 2010)
The aim of this research is to determine the influence of Capital Adequacy Ratio, Loan to Deposit Ratio, and Operational Cost to Operational Income of go public bank profitability that listing inIndonesiaâ€™s Stock Exchange during the period of 2000-2007. This research using the panel data that consist of time series data and cross sec66tion data of 21 go public banks inIndonesiawithGeneralized Least Squaremethod and Random Effect Model approach. The result of this research shows that the Capital Adequacy Ratio, Loan to Deposit Ratio, and Operational Cost to Operational Income had significantly influenced the profitability of go public banks in Indonesia during the period of 2000-2007.Â